Developing multilingual competence and cultural awareness through forms of non-formal learning: a contribution to sustainable employability, active citizenship and social inclusion - Simões, Anabela Valente (2022)
We live in a fast-changing world, where breakthrough technological advances have not just disrupted industries but also changed the way we live, work and learn to a degree humankind has never experienced before. As the modern workplace becomes ever more global and interconnected, proficiency in foreign languages (FL) assumes a fundamental role in international business relations. Simultaneously, being able to navigate culturally diverse environments, i.e., understanding how international stakeholders think, work, and express themselves through their attitudes and behaviours is of paramount importance as well. These challenges also raise pressing questions: How can we prepare learners for a global world in constant evaluation? How can we help them develop 21st-century skills as important as critical thinking, creativity, communication, adaptability, digital literacy and cross-cultural understanding? In May 2018, the Council of the European Union (CEU) adopted a Recommendation on Key Competences for Lifelong Learning, a framework that attempts to establish a common understanding of competences needed in the present moment and the future, by emphasising the inter-relatedness of knowledge, skills, attitudes and values. An important reference tool for education and training stakeholders, this recommendation identifies the following key competences: 1) Literacy competence; 2) Multilingual competence; 3) Mathematical competence and competence in science, technology and engineering; 4) Digital competence; 5) Personal, social and learning to learn competence; 6) Civic competence; 7) Entrepreneurship competence; and 8) Cultural awareness and expression competence. The EU Member States are, thus, encouraged to prepare their citizens for changing labour markets and active citizenship in more diverse, mobile, digital, and global societies, and to develop learning at all stages of life. While teacher-guided approaches will remain an important pedagogical practice, the main approach to teaching key competences is through providing learning environments that facilitate active learning, i.e., student-centred settings where open-ended problems and challenges can be solved through debate, experimentation, exploration, and creativity. This paper aims to narrate a non-formal activity carried out within a Business English Communication course taught at the Higher School of Technology and Management of the University of Aveiro (Portugal), in collaboration with an international group of volunteers from the European Solidarity Corps. This initiative sought to contribute to the development of some of the key competences for lifelong learning, especially multilingual skills and cultural sensitivity and expression, but also digital skills and personal and social skills of the participants.